Velvet - Hooper, Mary, 1948- (New York : Bloomsbury, 2012)
In Victorian London, orphaned Velvet leaves her backbreaking job in a steam laundry for the mysterious and exciting world of famed spiritualist Madame Savoya, who harbors dangerous secrets.
Includes bibliographical references (p. 323).
Kirkus Review
Publisher's Weekly
Kirkus Review, October 2012
Publisher's Weekly, October 2012
Young Adult.
Keywords: Orphans -- Juvenile fiction; Spiritualists -- Juvenile fiction; Historical fiction; Orphans -- Fiction; Spiritualists -- Fiction; Historical fiction; Orphans -- Fiction; Spiritualists -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile fiction; London (England) -- History -- 19th century -- Juvenile fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; London (England) -- History -- Fiction; Great Britain -- History -- 19th century -- Fiction; London (England) -- History -- Fiction; Historical fiction